PALEODEMOGRAPHY OF MEDIEVAL POPULATIONS IN KARACHAY-CHERKESSIA: INSIGHTS FROM THE KRASNOGORSK XII AND KRASNOGORSK XIIb BURIAL GROUNDS - Boruckaa, Svetlana Borisovna; Vasil'ev, Sergej Vladimirovic; Frizen, Sergej Ur'evic (History, Archeology and Ethnography of the Caucasus, 2024)
This study presents a paleodemographic analysis of two settlements and burial grounds, Krasnogorsk XII and Krasnogorsk XIIb, located in the Ust-Dzhegutinsky district of the Karachay-Cherkessia Republic of Russia. Both sites belong to a single cultural circle and are preliminary dated to the late 12th – early 13th centuries. The analysis is based on a large and representative sample from each burial ground. The results reveal high mortality rates in early childhood, with peaks occurring in the first five years of life. Infant mortality, particularly among newborns, is exceptionally high in both groups. Average life expectancy is low, estimated at 21.38 years in Krasnogorsk and 19.13 years in Krasnogorsk XIIb, suggesting significant demographic challenges in both groups. Notably, average life expectancy for adult males and females is similar – around 37 years. Sex ratios differ between the groups: Krasnogorsk exhibits near parity, while Krasnogorsk XIIb shows a slight male bias (10% more men). This pattern might reflect higher female mortality, particularly among young girls and newborns. Interestingly, Krasnogorsk XIIb also displays a higher proportion of individuals of both sexes belonging to the final age cohort, i.e., exceeding 50 years old.
Keywords: paleodemography; age cohort; paleodemographic indices; average life expectancy; infant mortality; final age cohort